2015
DOI: 10.1039/c5ra15652a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and membrane stress-mediated antibacterial activity of WS2and rGO-WS2nanosheets

Abstract: We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 44 publications
0
49
1
Order By: Relevance
“…Navale et al. compared the antibacterial ability of WS 2 nanosheets, rGO, and WS 2 ‐rGO nanocomposites . They found that although all the above materials can induce ROS‐independent oxidative stress and membrane rupture, WS 2 ‐rGO nanocomposites are capable of generating .…”
Section: Antibacterial Activity Of 2d Materials Beyond Gmsmentioning
confidence: 99%
“…Navale et al. compared the antibacterial ability of WS 2 nanosheets, rGO, and WS 2 ‐rGO nanocomposites . They found that although all the above materials can induce ROS‐independent oxidative stress and membrane rupture, WS 2 ‐rGO nanocomposites are capable of generating .…”
Section: Antibacterial Activity Of 2d Materials Beyond Gmsmentioning
confidence: 99%
“…22 Shinde and co-workers also demonstrated that WS 2 can cause retardation in bacterial growth and inhibitory effect on bacterial strains. 40 On the other hand, there are also conicting reports in literature regarding these TMDCs' antibacterial activities. For instance, Chae and coworkers suggested that MoS 2 and WS 2 only displayed limited cytotoxicity and genotoxicity, with no signicant deleterious effect to cellular viability.…”
Section: -38mentioning
confidence: 99%
“…The high antibacterial rates against S. aureus and E. coli indicated a quite high antibacterial efficiency of the WS 2 laminar membrane, even after short‐term contact (1 h). The proposed mechanism for this marked antibacterial property is that the WS 2 nanosheets retarded the bacterial growth by deformation of the bacterial cell and damage of the cell wall on the basis of the reported results …”
Section: Resultsmentioning
confidence: 78%